Structure bound guide to access cavity preparation for molar root canal treatment - Sundaresan Balagopal; Charanya Chandrasekaran (Wolters Kluwer Medknow Publications, 2020)
A good access cavity preparation is the gateway to success in endodontic treatment. This article presents occlusal landmarks that can be used as the boundary for the endodontic access at the occlusal surfaces of maxillary and mandibular molars. Further this article gives a structure or landmark guided three simple stages of preparation to reach the pulp chamber. This assures an ideal access cavity reducing the risk of dentin gouging and eliminating iatrogenic deleterious events. All canal orifices will be within this boundary and can often be located easily.